SURVEI RISIKO KESEHATAN KERJA PETUGAS GIZI DI RUMAH SAKIT ISLAM KABUPATEN KARAWANG - Wieke Widhiantika; Jumaedi, Jumaedi; Chaerani Tri Yuliana; Yasin Azhari; Muhidin, Muhidin; Wendi Darmawan (Bajang Institute, 2024)
Occupational health risks among nutrition staff in hospitals are often overlooked in occupational health and safety (OHS) policies that tend to focus more on medical personnel. This study aims to identify and evaluate the occupational health risks faced by nutrition staff at the Islamic Hospital of Karawang Regency and provide recommendations for more effective risk mitigation. The research approach used is a quantitative descriptive method with a cross-sectional design. Data collection was carried out through a survey using structured questionnaires distributed to all nutrition staff working at the hospital. The study results indicate that the most significant occupational health risk is work-related stress (30%), followed by chemical exposure (25%), poor ergonomics (20%), biological exposure (15%), and physical hazards (10%). The high risk of work-related stress is caused by excessive workloads, lack of management support, and strict service demands. Chemical exposure, such as from detergents and disinfectants, can cause skin irritation, respiratory problems, and other health issues. Poor ergonomics related to inappropriate working positions and unsuitable equipment use leads to musculoskeletal disorders, such as back pain. Biological exposure can result from inadequate hygiene standards and unsafe food handling, while physical hazards include injuries from unsafe kitchen equipment. This study recommends comprehensive interventions to reduce occupational health risks, including regular training on stress management and safe chemical use, improving the work environment to be more ergonomic, and strengthening hygiene standards. Implementing a more inclusive and data-driven OHS policy can improve the well-being of nutrition staff, which, in turn, will enhance the quality of healthcare services in the hospital. This aligns with findings that